SIMILE USED IN LENKA’S SONG EVERYTHING AT ONCE - Syarifah Syarifah; M. Manugeren; Purwarno Purwarno (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2020)
The research was related to figurative language but the researchers focused on simile, aimed at identifying the dominant type of simile used based on the theory put forward by Kennedy and Giola. Simile is a comparison of one thing to another which is always listed because the words "like" or as are used. Simile is also commonly used in song lyrics and this is referred to as the object of the research, that is the song lyrics taken by Lenka’s song Everything at Once. The researchers take this song because all the lyrics are full of similes, from the beginning to the end of the song. Qualitative content analysis as the use of replicable and valid methods to make specific inferences from the text to other circumstances or properties of the source under the Descriptive Qualitative Approach, pioneered by Krippendorff is applied here. The results show that there are two types of simile in this song and the dominant types used in this song is close simile.